Stress, sex, and addiction: potential roles of corticotropin-releasing factor, oxytocin, and arginine-vasopressin - Bisagno, Veronica (2014)
Stress sensitivity and sex are predictive factors for the development of neuropsychiatric disorders. Life stresses are not only risk factors for the development of addiction but also are triggers for relapse to drug use. Therefore, it is imperative to elucidate the molecular mechanisms underlying the interactions between stress and drug abuse, as an understanding of this may help in the development of novel and more effective therapeutic approaches to block the clinical manifestations of drug addiction. The development and clinical course of addiction-related disorders do appear to involve neuroadaptations within neurocircuitries that modulate stress responses and are influenced by several neuropeptides. These include corticotropin-releasing factor, the prototypic member of this class, as well as oxytocin and arginine-vasopressin that play important roles in affiliative behaviors. Interestingly, these peptides function to balance emotional behavior, with sexual dimorphism in the oxytocin/arginine-vasopressin systems, a fact that might play an important role in the differential responses of women and men to stressful stimuli and the specific sex-based prevalence of certain addictive disorders. Thus, this review aims to summarize (i) the contribution of sex differences to the function of dopamine systems, and (ii) the behavioral, neurochemical, and anatomical changes in brain stress systems.